Longterm Follow-up on Patients with Subdural Effusions - Taslim S. Sutomenggolo; Sofjan Ismael; S.K. Hendarto; S.M. Lumbantobing (Paediatrica Indonesiana, 1978)
Seventy-two patients with subdural effusions who had been hospitalized in the Department of Child Health, Dr. Cipto Mangunkusumo General Hospital, Jakarta, were followed up for at least one year. Of the 72 patients, 35 were included nn this evaluation. Of the 35 patients, 16 were caused by purulent meningitis, and 19 by other diseases. On follow up examination comparison was made between the prognosis of patients with subdural effusions which dried in less than 2 weeks and subdural effusions which dried in more than 2 weeks or the patient who was asked to be discharged before the subdural effusions dried. The conclusion is that the former group has less neurological deficit, epileptic seizures, motoric and mental retardation than the latter. The prognosis is worse in patients with subdural effusions of long duration.